From Phenotype to Molecules: Unveiling the Genetic and Immunological Bridges Between Autoimmune Diseases and Vitiligo - Hu Y; Wang SB; Wang K; He MJ (Dove Medical Press, 2024)
Yuan Hu,1,* Shao-Bo Wang,1,* Kun Wang,2 Ming-Jie He2 1Suining Central Hospital, Suining, Sichuan, People's Republic of China; 2First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People's Republic of China*These authors contributed equally to this workCorrespondence: Ming-Jie He, Email hmj15238917691@163.comIntroduction: Vitiligo is an autoimmune disease characterized by the loss of skin pigmentation. This study aims to explore genetic associations between vitiligo and 21 autoimmune diseases using Mendelian randomization (MR) analysis, with a focus on identifying potential risk and protective factors.Methods: We performed univariable and multivariable Mendelian randomization analyses to assess the causal associations between 21 autoimmune diseases and vitiligo. Confounding factors, including smoking, alcohol consumption, and Body Mass Index (BMI), were integrated into the multivariable analysis. Strongly associated single nucleotide polymorphisms (SNPs) were mapped to genes, followed by Summary-data-based Mendelian Randomization (SMR) analysis with expression Quantitative Trait Loci (eQTL) and methylation Quantitative Trait Loci (mQTL) data. Risk and protective factors were further identified by evaluating inflammatory mediators and immune cell phenotypes.Results: The MR analysis identified seven autoimmune diseases with potential causal associations with vitiligo. However, after accounting for confounding factors, only Hashimoto's thyroiditis and type 1 diabetes maintained genetic associations with vitiligo. Gene mapping revealed 25 intersecting genes between these two diseases and vitiligo. SMR analysis confirmed Sulfite Oxidase (SUOX) as a protective gene across multiple tissues. Furthermore, several inflammatory factors were identified as risk factors, including C-X-C motif chemokine ligand 9 (CXCL9), C-X-C motif chemokine ligand 10 (CXCL10), Tumor Necrosis Factor (TNF), and Signaling Lymphocytic Activation Molecule (SLAM). In contrast, Osteoprotegerin (OPG) was identified as a protective factor.Discussion: This study provides novel insights into the shared molecular mechanisms linking vitiligo with other autoimmune diseases. The identification of SUOX as a common protective gene and the discovery of specific inflammatory and immune-related factors may facilitate future therapeutic strategies.Keywords: autoimmune diseases, causality, Mendelian randomization, sulfite oxidase, vitiligo